Proportion of pulmonary tuberculosis cases diagnosed at different levels of health care across fourteen districts of Kerala - Vinod, Vaishnavy S.; George, Leyanna Susan; Joy, Aleena; Mathew, Minu Maria; K., Vijayakumar; Kunoor, Akhilesh; Kumar, Anil (International Journal Of Community Medicine And Public Health, 2020)
Background: It is estimated that 10.4 million cases and 1.7 million deaths occur due to tuberculosis (TB) globally. More than one quarter of TB cases and TB-related deaths worldwide occur in India each year. Kerala's TB incidence is estimated to be 67 cases per 100,000. Objective was to estimate the proportion of Pulmonary TB cases diagnosed at different levels of the health care system across all the fourteen districts of Kerala from January to September 2019. Methods: A secondary data analysis was conducted on information obtained from the NIKSHAY portal from January to September 2019. Proportion of cases detected at PHC, CHC, THQ, District hospital and other tertiary care facilities was computed. Statistical analysis was performed using statistical package of social sciences (SPSS) version 23.0. Results: The maximum number of new TB cases (70.8%) was being detected at the primary care level, while 20.3% of new cases were detected from tertiary care centres and 8.9% from secondary care centres. At the primary healthcare level, the maximum number of newly diagnosed TB cases was reported from Wayanad district (88.0%) while, in the secondary and tertiary care levels, Kollam district was found to diagnose the maximum number of new TB cases (24.0% and 48.4% respectively). Conclusions: In this study, majority of the new TB cases were being diagnosed at the Primary health care level. However, in few districts the secondary and tertiary care centres were found to be diagnosing a greater number of cases.